"Doing good" while serving customers: Charting the social entrepreneurship and marketing interface. Issue 2 (16th October 2017) - Roundy, Philip T.
Abstract : Purpose: Social entrepreneurship represents an unconventional, but increasingly prevalent, activity in developed and emerging economies. Social entrepreneurs devise novel business models that blend business and social missions with the aim of (co-)producing value with two primary stakeholder groups, beneficiaries and customers. Although interactions between social entrepreneurs and their beneficiaries are well-studied, the relationship between social ventures and consumers has received almost no extended attention. Design/methodology/approach: Using a qualitative, partially-inductive approach based on interviews with 40 social entrepreneurs, a study of how social entrepreneurs market their ventures to consumers was conducted. Findings: Findings reveal the ways in which marketing is relevant for social entrepreneurs, the unique challenges and opportunities entrepreneurs face in their interactions with customers, and the tactics entrepreneurs use to understand and educate their consumers. Originality/value: The study's findings contribute to work on social entrepreneurship and the entrepreneurship and marketing interface and have practical implications for social entrepreneurs.